Underlying Factors for Attitude Formation: Study on Secondary School Teachers - Basnet, Hom Bahadur; Sherpa, Dawa (Rupantaran: A Multidisciplinary Journal, 2020)
Teachers’ roles are more significant in the students learning process. Thus, a teacher’s attitude towards teaching and his job satisfaction have a great impact upon students’ learning and their successes. Teacher’s attitude towards their job affects student’s achievements, student’s educational outcomes. This study aims to explore the underlying factor in attitude formation of secondary school teachers in Dolakha district. For this purpose, this study has designed the research question focused on what are the determining factors for attitude formation of secondary school teachers? In this context phenomenological research design enables me to explore the participants’ perceptions regarding their attitude formation towards their job. This study concluded that job security is a significant part for the attitude formation. If teachers are permanent in job nature his attitude towards his job and profession would be positive and if not, he would be negative. Only satisfied and motivated individuals perform the task well. Social values and judgement are the factors for attitude formation. The home access job and facilities of provident fund freedom of workplace create the positive attitude and absence of it make negative attitude.